Pengembangan Modul Berbasis Problem Based Learning (PBL) Pada Materi Operasi Aljabar Di Kelas VII - Arpani Ulang; Suharti; Thamrin Tayeb (Department of Mathematics Education, 2022)
This study aims to develop a valid, practical, and effective problem-based learning-based module on algebraic operation material in class VII of SMPN 4 Bontoramba. This study used the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation) with the research subjects as many as 20 students in class VII of SMPN Bontoramba. The instruments used in this study were expert validation sheets, teacher response questionnaires, student response questionnaires, teacher ability observations, learning outcomes tests, and learning outcomes tests (THB). Based on the results of the research that has been carried out, it is obtained: validation results obtained a value of 4 which is in the valid category; : validation results obtained a value of 4 which is in the valid category; Practicality results are in the very positive category because the average percentage of student responses reaches 83.45% and teacher responses reach 92.5%; and the result of effectiveness with the average percentage for the teacher's ability to manage learning is 4.65 is in the excellent category, the average percentage of student activity is 82.3% is in the good category, and The percentage of student learning completion is in the high category and reaches classical completion which is 79.5%.